Exploring the Future of Climate Change and Political Violence in Indonesia - Ayanoglu, Harun Talha (Global Strategis, 2024)
This article investigates the complex dynamics between climate change and political violence, emphasizing their multifaceted relationship. Resorting to the three-pillar model distilled from the climate-conflict literature, it explores how climate change interacts with existing socioeconomic and political vulnerabilities, amplifying the risk of conflict. Focusing on Indonesia as a case study, the article examines the intersection of climate exposure, sociopolitical fragility, and terrorism. The country's exposure to sea-level rise, flooding, and water stress heightens concerns over food and water security, while the persistent threat of religiously motivated terrorism exacerbates the complexity. As global climate change accelerates, the potential for increased political violence grows. Mitigating these vulnerabilities and strengthening governance will be essential for Indonesia's resilience in the face of climate change. Keywords: Climate change, Political violence, terrorism, Indonesia Artikel ini menyelidiki dinamika yang rumit antara perubahan iklim dan kekerasan politik, dengan menekankan pada hubungan multi- dimensi yang dimiliki. Artikel ini meneliti bagaimana interaksi antara perubahan iklim dan kerentanan sosial ekonomi serta politik yang ada dapat memperbesar resiko konflik yang terjadi dengan menggunakan model tiga pilar yang didapatkan dari literatur tentang iklim dan konflik. Indonesia sebagai fokus dari studi kasus, artikel ini meneliti hubungan antara paparan iklim, kerapuhan sosial politik, dan terorisme. Paparan negara terhadap kenaikan permukaan air laut, banjir, dan kelangkaan air meningkatkan kekhawatiran terhadap ketersediaan pangan dan air, sementara ancaman terorisme yang terus berlanjut turut memperumit keadaan. Seiring dengan percepatan perubahan iklim global, potensi kekerasan politik yang terjadi turut meningkat. Upaya mitigasi terhadap kerentanan ini dan dengan memperkuat pengelolaan yang dilakukan akan menjadi penting untuk Indonesia dalam menghadapi perubahan iklim yang terjadi. Kata-kata Kunci: Perubahan Iklim, Kekerasan Politik, Terorisme, Indonesia